2023
DOI: 10.35534/natanthropol.2023.10004
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale Genetic Structure of Geographically Distinct Patrilineal Lineages Delineates Southward Migration Routes for Han Chinese

Abstract: The Han Chinese (HAN) represent the world's largest ethnic group, and their genetic structure has been the focus of numerous studies. Yet previous studies failed to draw out finer population stratification of patrilineal HAN, due to limitations in sample size and genetic marker density. This essay employs a Y-haplogroup frequency dataset from virtually whole China aiming to draw out a detailed genetic structure of the patrilineal HAN. We provide an overview of the Y chromosome haplogroup distributions, and fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Using the uniparental markers, Wen et al revealed the southward demic diffusion of the Han Chinese with sex-biased admixture as the differentiation of the genetic contribution of northern Han to southern Han between the paternal and maternal lineages (Wen et al 2004a). Subsequently, the phylogeographic pattern observed in the Y-chromosome presented that the genetic component of the Han Chinese was intricate and diverse, along with different paternal lineages (Xue et al 2006;Xue et al 2008;Zhong et al 2011;Lang et al 2019;Song et al 2019;Tao et al 2023). Meanwhile, autosomal DNA-based research identified different ancestral components among geographically diverse Han Chinese populations (Chen et al 2019;He et al 2020;He et al 2021;Yao et al 2021;He et al 2022;Wang et al 2022c).…”
Section: Introductionmentioning
confidence: 99%
“…Using the uniparental markers, Wen et al revealed the southward demic diffusion of the Han Chinese with sex-biased admixture as the differentiation of the genetic contribution of northern Han to southern Han between the paternal and maternal lineages (Wen et al 2004a). Subsequently, the phylogeographic pattern observed in the Y-chromosome presented that the genetic component of the Han Chinese was intricate and diverse, along with different paternal lineages (Xue et al 2006;Xue et al 2008;Zhong et al 2011;Lang et al 2019;Song et al 2019;Tao et al 2023). Meanwhile, autosomal DNA-based research identified different ancestral components among geographically diverse Han Chinese populations (Chen et al 2019;He et al 2020;He et al 2021;Yao et al 2021;He et al 2022;Wang et al 2022c).…”
Section: Introductionmentioning
confidence: 99%